Distribution of cardiovascular risk in type 2 diabetes: results of an analysis using data from the CAPTURE study. (14th October 2021) - Oestergaard, H B; Hengeveld, E M; Honore, J B; Humphreys, V; Mach, F; Westerink, J; Yadav, G; Mosenzon, O
Abstract: Introduction: Cardiovascular disease (CVD) is the leading cause of mortality in people with type 2 diabetes (T2D). CAPTURE, a non-interventional, cross-sectional study conducted across 13 countries in 2019, collected demographic and clinical characteristics in almost 10, 000 adults with T2D in primary or secondary care. Less than 25% of patients with established CVD treated with a glucose-lowering agent received an agent with demonstrated benefit in cardiovascular (CV) risk reduction, such as a glucagon-like peptide-1 receptor agonist (GLP-1 RA) or a sodium–glucose co-transporter-2 inhibitor (SGLT-2i). 1 It is not known whether this is linked to estimated 10-year and lifetime CV risk. Purpose: To estimate the CV risk distribution in the CAPTURE population using the Diabetes Lifetime-perspective prediction (DIAL) model, and to assess treatment patterns by CV risk. Methods: The DIAL model is an externally validated competing risk adjusted model for predicting CV risk in patients with T2D, calculating absolute 10-year and lifetime risk of myocardial infarction, stroke or cardiovascular death, and life-expectancy free of a CVD event. Patient-level data from CAPTURE (age, sex, body mass index, smoking status, HbA1c, CVD history, T2D duration, clinical parameters and treatment history) were used in the DIAL model. Missing data were imputed by region using predicted mean matching. High risk was defined as 10-year risk >10%, and lifetime risk >50%. Results: Data from 9457 patients with T2D aged 30–85 years were included in the analyses. There was a wide distribution of both 10-year and lifetime risk, with higher risk in patients with a history of CVD (n=2914) than in those without (n=6543). Among patients with a history of CVD, 96% had a 10-year risk of CVD >10% and 81% had a lifetime risk of CVD >50% (Figure). In patients with CVD and a high 10-year risk of recurrent CVD, 81% had a lifetime risk of recurrent CVD >50%. In patients without history of CVD, 14% had a 10-year risk >10% and only 1% had a lifetime risk >50% (Figure). Among patients without previous CVD but with a high 10-year risk of CVD, only 4% had a lifetime risk >50%. Of the patients with CVD, 10% received a GLP-1 RA and 18% received an SGLT-2i. Similarly, of patients with CVD and a high 10-year risk of recurrent CVD, 10% received a GLP-1 RA and 17% received an SGLT-2i. Among patients without CVD, 11% received a GLP-1 RA and 16% received an SGLT-2i, and among patients without current CVD but at a high 10-year risk of CVD, 12% received a GLP-1 RA and 16% received an SGLT-2i. Conclusion: There is a wide distribution of CVD risk in the CAPTURE population, and only a minority of patients at high risk of CVD received a glucose-lowering agent with demonstrated benefit in CV risk reduction. Discussing with patients the 10-year and lifetime risks, and the CV benefit to be gained from interventions, can enhance shared decision making. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Funded by Novo Nordisk A/S